Morphological and molecular diversity of thermosensitive genic male sterile lines in rice (Oryza sativa L.) - K. Sai Rekha1*, R. Saraswathi1, M. Kumar1, S. Manonmani1, M. Raveendran2 and S. Robin1 (Electronic Journal of Plant Breeding, 2021)
An investigation was taken up to study the genetic relationship of thermosensitive genic male sterile lines developed at Tamil Nadu Agricultural University, Coimbatore using morphological traits and SSR markers. Morphological and floral traits revealed a significant and wide genetic variation among TGMS lines. SSR markers survey using 100 SSR markers revealed that 27 were polymorphic, amplifying a total of 71 alleles with an average of 2.67 alleles. Based on the morphological characters, TNAU 18S exhibited better performance for a number of tillers per plant, angle of glume opening and panicle length and TNAU 45S expressed good floral characters. Cluster analysis differentiated six TGMS lines into four clusters. There is a difference in the dissemination of TGMS lines into different groups based on molecular and morphological data may be due to selection pressure, sampling error and genetic drift. The diverse TGMS lines obtained from cluster analysis could be used directly in the crossing program for the production of high heterotic two-line rice hybrids.